2003
DOI: 10.1073/pnas.1432634100
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the clathrin-assembly gene Picalm are responsible for the hematopoietic and iron metabolism abnormalities in fit1 mice

Abstract: Recessive N-ethyl-N-nitrosourea (ENU)-induced mutations recovered at the fitness-1 (fit1) locus in mouse chromosome 7 cause hematopoietic abnormalities, growth retardation, and shortened life span, with varying severity of the defects in different alleles. Abnormal iron distribution and metabolism and frequent scoliosis have also been associated with an allele of intermediate severity (fit1 4R ). We report that fit1 4R , as well as the most severe fit1 5R allele, are nonsense point mutations in the mouse ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…12 These domains include the epsin N-terminal homology (ENTH) domain (Asp-Pro-Phe), a DPF (ASP-Pro-Phe) motif, an NPF (Asn-Pro-Phe) motif and type I and II clathrin-binding sequences (CBS I and II). [13][14][15] The predicted CALM protein is similar to the neuronal specific monomeric clathrin assembly protein AP180, which was first identified in coated vesicles of bovine brain. 16,17 CALM homologues have been identified in rat, mouse and cow.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…12 These domains include the epsin N-terminal homology (ENTH) domain (Asp-Pro-Phe), a DPF (ASP-Pro-Phe) motif, an NPF (Asn-Pro-Phe) motif and type I and II clathrin-binding sequences (CBS I and II). [13][14][15] The predicted CALM protein is similar to the neuronal specific monomeric clathrin assembly protein AP180, which was first identified in coated vesicles of bovine brain. 16,17 CALM homologues have been identified in rat, mouse and cow.…”
Section: Introductionmentioning
confidence: 96%
“…23 Finally, point mutations in the CALM gene led to ineffective hematopoiesis, functional iron deficiency and altered growth in mice, suggesting that CALM may play a role in endocytosis-mediated iron transport. 15 In addition to an established role in endocytosis, a recent study suggested that CALM may interact with nuclear proteins. 24 In this study, the novel protein CATS (CALM interacting protein, expressed in thymus and spleen) was shown to interact with a region of the CALM protein that is retained in the CALM-AF10 fusion protein and increased the nuclear localization of both CALM and a CALM-AF10 fusion protein.…”
Section: Introductionmentioning
confidence: 99%
“…Klebig et al reported fit1 mice, with mutations in PICALM, showed a decreased lifespan and growth retardation, along with numerous haematopoietic abnormalities, manifesting in severe anaemia and a decreased white blood cell count (Klebig et al 2003), suggesting potential roles for PICALM in growth, haematopoiesis and iron metabolism. There are a number of different fit1 mice, each with a different mutation within PICALM, and with phenotypic severity related to the severity of the mutations (Klebig et al 2003).…”
Section: Picalm -The Proteinmentioning
confidence: 99%
“…There are a number of different fit1 mice, each with a different mutation within PICALM, and with phenotypic severity related to the severity of the mutations (Klebig et al 2003). …”
Section: Picalm -The Proteinmentioning
confidence: 99%
See 1 more Smart Citation